Follow me [large type] : a novel - Scott, Joanna, 1960- (Thorndike Press large print basic, 2009)
On a summer day in 1946, Sally Werner, the precocious daughter of hardscrabble Pennsylvania farmers, accepts her cousin Daniel's invitation to ride his new motorcycle. Like so much of what follows in Sally's life, it's a decision driven by impulse and a thirst for adventure, a decision with dramatic and far-reaching consequences. Soon Sally abandons her newborn baby and her home and embarks on an odyssey of self-creation that spans six decades, the story of which she entrusts to only one person: her granddaughter and namesake.